A.I.M Enterprise: A.I. fitness mirror / Adil Ariff ...[et al.] - Ariff, Adil; Arham, Ammar; Rodzeaimy, Muhammad Firdaus; Zakaria, Muhammad Haziq Farhan (2023)
This business is based on partnership where it consists of four (4) members which hold important positions in the company such as General Manager Also acts as an Administration Manager, Marketing Manager, Operational Manager and financial Manager. The name of our company is A.I.M Enterprise. A.I.M is coming from the word Artificial Intelligence Mirror. The word ‘Artificial intelligence’ is carry the meaning of simulation of human intelligence processes by computer systems that include expert system, natural processing, speech recognition and machine vision. This system is work by ingesting large amounts of labelled training data and analyzing the data for correlations and patterns to make prediction about future. This business will connect the mirror to the A.I system to represent the functionality of our products. We will provide our customer an artificial intelligence mirror that will show the correct posture of exercise activity to make sure the total calories that burn when doing the activity is 100% same with the burn calories that has set to the exercise activities. This A.I Mirror has their own cameras to detect the motion of the user body and make a command if the user did not make 100% correct movement according to health ministration. A.I.M will be starting at Taman Kota Masai, 87000 Pasir Gudang, Johor. We choose to start our business here in Pasir Gudang, Johor because it has a lot of factory and workshop that have specialist to make our product become success. This can help to easier our process when make cutting, A.I system and more works for our products.